2002
DOI: 10.1111/j.1471-0528.2002.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of preterm delivery in women from different ethnic groups

Abstract: Objective To examine whether routinely measured variables explained the increased risk of preterm delivery in some UK ethnic groups. Design Cross sectional study of deliveries recorded in the Child Health Record System. Setting North Birmingham, UK.Population All North Birmingham women delivering singletons, 1994-1997 inclusive. Method Logistic regression.Main outcome measures Odds ratio (OR) and 95% confidence interval (CI) for preterm delivery, defined as less than 37 weeks, less than 34 weeks and less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 23 publications
4
38
2
6
Order By: Relevance
“…Our data do not show any association with mother's education level or employment during pregnancy [24][25][26]. However, the number of women of low level of education in our study was small, such that the analysis had little power.…”
Section: Discussionmentioning
confidence: 47%
“…Our data do not show any association with mother's education level or employment during pregnancy [24][25][26]. However, the number of women of low level of education in our study was small, such that the analysis had little power.…”
Section: Discussionmentioning
confidence: 47%
“…We share the opinion of other authors [18,19] that a direct relation exists between the degree of racial integration and the immigrant’s health and are aware that social studies have already shown how much a good integration policy exerts a protective effect upon perinatal health [20]. …”
Section: Discussionmentioning
confidence: 99%
“…The above situations thus have created a conflict in the maternal/fetal relationship. When compared with Caucasian infants, African infants have shorter average gestational length [54], [55] and more frequent meconium-stained amniotic fluid [56], all of which have been hypothesized to be related to the smaller pelvic sizes of Africans compared to Caucasians. Interestingly, Asian women have even smaller pelvises than the Africans [56] and less pelvic organ mobility than the Caucasians [57].…”
Section: Discussionmentioning
confidence: 99%